2012
DOI: 10.1016/j.jcma.2012.06.012
|View full text |Cite
|
Sign up to set email alerts
|

Primary hyperparathyroidism in children and adolescents

Abstract: Primary hyperparathyroidism (PHPT) is a common endocrine disorder in adults in whom the typical presentation is incidentally discovered as asymptomatic hypercalcemia. PHPT is much less common in children and adolescents, but has greater morbidity in this age group, as most young patients with PHPT will have symptomatic hypercalcemia or complications such as kidney stones, abdominal pain, and skeletal fragility. An important feature of PHPT in younger patients is the relatively high prevalence of germline inact… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
106
0
7

Year Published

2015
2015
2023
2023

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 99 publications
(117 citation statements)
references
References 83 publications
4
106
0
7
Order By: Relevance
“…Unlike previous pediatric reviews, we found a higher incidence in females, similar to the experience in adult PHPT. The proportion of asymptomatic patients was higher in our series than that described in 2 recent pediatric reviews (24% vs. 15%) but it was lower than that reported in adults [3, 4]. This is consistent with recent reviews that indicate that PHPT at a younger age is usually more symptomatic at diagnosis [5, 29].…”
Section: Discussionsupporting
confidence: 87%
“…Unlike previous pediatric reviews, we found a higher incidence in females, similar to the experience in adult PHPT. The proportion of asymptomatic patients was higher in our series than that described in 2 recent pediatric reviews (24% vs. 15%) but it was lower than that reported in adults [3, 4]. This is consistent with recent reviews that indicate that PHPT at a younger age is usually more symptomatic at diagnosis [5, 29].…”
Section: Discussionsupporting
confidence: 87%
“…It has an incidence of 2-5 per 100,000 (compared with 1 in 1,000 in adults), and there is an equal sex distribution [4] . Approximately 20% of cases of PHPT present in the neonatal period, and the remaining 80% present during adolescence [5] .…”
Section: Primary Hyperparathyroidismmentioning
confidence: 99%
“…At presentation of PHPT, children are usually symptomatic, with only 15% of cases diagnosed serendipitously as asymptomatic hypercalcaemia [4] . Children typically present with signs or symptoms of hypercalcaemia, skeletal complications, and/or nephrolithiasis (but see [19][20][21][22].…”
Section: Primary Hyperparathyroidismmentioning
confidence: 99%
See 2 more Smart Citations